1999
DOI: 10.1021/es981005n
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Vehicle Particle Size Distributions:  Comparison of Steady State, FTP, and US06 Measurements

Abstract: Factors influencing the number and size of tailpipe particles from port injection, spark ignition vehicles are examined by comparing emissions recorded during steady-state operation and those obtained from FTP and US06 drive cycles. Size distributions are measured using the scanning mobility particle sizer (SMPS) and the electrical low-pressure impactor (ELPI). Steady-state particulate emissions are examined as a function of vehicle speed and air to fuel ratio. The emission rates increase moderately with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 12 publications
8
59
0
Order By: Relevance
“…27 Gasoline engines have much lower PM mass emissions than diesel engines. Tailpipe particle emission mass is as low as 0.1 mg/mi, and the baseline number concentration is 10 5 -10 6 particles/cm 3 , 264,266 which is consistent with the reported accumulation mode particle size. Graskow et al 264 reported that the particle number from gasoline engines is highly unstable and that they observed intermittent spikes in particle number up to 2 orders of magnitude above the baseline.…”
Section: Internal Combustion Enginessupporting
confidence: 86%
See 1 more Smart Citation
“…27 Gasoline engines have much lower PM mass emissions than diesel engines. Tailpipe particle emission mass is as low as 0.1 mg/mi, and the baseline number concentration is 10 5 -10 6 particles/cm 3 , 264,266 which is consistent with the reported accumulation mode particle size. Graskow et al 264 reported that the particle number from gasoline engines is highly unstable and that they observed intermittent spikes in particle number up to 2 orders of magnitude above the baseline.…”
Section: Internal Combustion Enginessupporting
confidence: 86%
“…Table 5 summarizes exhaust measurements of particle size and number concentration data from selected studies of diesel and gasoline engines. 27,[260][261][262][263][264][265][266] The exhaust tailpipe data show that IC engines are a source of particles smaller than 100 nm at initial concentrations greater than 10 6 /cm 3 , which is consistent with measurements of ambient particle size distributions at various distances from urban highways. 267,268 The sizes of diesel particulate emission can be approximated by a bimodal lognormal distribution.…”
Section: Internal Combustion Enginessupporting
confidence: 62%
“…Johnson et al (2005) found that gasoline engines emit lesser particulate mass as compared to diesel engines however gasoline particulates are significant from number stand-point. Several other researchers demonstrated that the fraction of particles emitted in the nuclei mode is higher in gasoline engines compared to diesel engines (Graskow et al, 1998;Maricq et al, 1999). Under lean engine operating conditions, elemental carbon or soot does not form in large quantities to be of any serious importance for gasoline engines however it is formed in larger quantities for rich fuel-air mixture combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a companion paper (Ban-Weiss et al, 2008) indicate that on average, diesel engines emit an order of magnitude more PM mass than gasoline engines, per unit of fuel burned. But the relative importance of gasoline vehicles as a source of PM is higher when considering number rather than mass emissions; the fraction of particles that are emitted in the nuclei mode is higher in gasoline vs. diesel engines (Graskow et al, 1998;Maricq et al, 1999a;Maricq et al, 1999b;Kayes et al, 2000;Johnson et al, 2005). However, variations in sampling protocols, both in terms of driving cycles and PM measurement methods (Ayala et al, 2003), and a lack of definitive "real-world" studies, have made direct comparison of gasoline vs. diesel particle number emissions difficult.…”
Section: Introductionmentioning
confidence: 99%